LEGAL RECONSTRUCTION OF CORPORATE SOCIAL RESPONSIBILITY: PREVENTING AN ENVIRONMENTAL CONFLICTS - Any Ismayawati; Luqman Nurhisam (Jurnal Pembaharuan Hukum, 2022)
The conflicts between companies and communities have a massive impact and even cause national instability so that it becomes counter-productive with development goals. In this regard, this study examines why there are many environmental conflicts between companies and communities, why many companies do not implement CSR, and how the legal reconstruction of CSR that can prevent environmental conflicts. This study aims to find out why there are so many conflicts between companies and the community? To find out why many companies do not implement CSR? and how to reconstruct CSR regulations in order to prevent environmental conflicts between companies and communities. The approach method used a normative juridical approach. The results of this study show that conflicts between companies and communities are frequent and difficult to resolve because the current CSR regulations provide opportunities for companies to exploit natural resources and override the protection of human resource interests that should be the subject of development rather than the object of development. Many companies do not implement CSR because CSR regulations are still appealing and there are no criminal sanctions, and there is no legal unification. Therefore, it is necessary to reconstruct CSR regulations in order to prevent environmental conflicts.